2018
DOI: 10.1111/pce.13427
|View full text |Cite
|
Sign up to set email alerts
|

Pollen, ovules, and pollination in pea: Success, failure, and resilience in heat

Abstract: Field pea (Pisum sativum), a major grain legume crop, is autogamous and adapted to temperate climates. The objectives of this study were to investigate effects of high temperature stress on stamen chemical composition, anther dehiscence, pollen viability, pollen interactions with pistil and ovules, and ovule growth and viability. Two cultivars ("CDC Golden" and "CDC Sage") were exposed to 24/18°C (day/night) continually or to 35/18°C for 4 or 7 days. Heat stress altered stamen chemical composition, with lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 37 publications
4
57
1
1
Order By: Relevance
“…The same phenomenon was observed in sorghum, and thus, pollen was more susceptible to heat stress compared to pistil since pollen was more sensitive to oxidative damage—increasing the ROS accumulation and decreasing antioxidant enzyme activity (Djanaguiraman et al., ). Our previous research also indicated that male floral organs in field pea were more sensitive to heat stress compared to female floral counterparts, because ovule viability was affected by heat stress at p < 0.10 not at p < 0.05 like pollen (Jiang, et al., ).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The same phenomenon was observed in sorghum, and thus, pollen was more susceptible to heat stress compared to pistil since pollen was more sensitive to oxidative damage—increasing the ROS accumulation and decreasing antioxidant enzyme activity (Djanaguiraman et al., ). Our previous research also indicated that male floral organs in field pea were more sensitive to heat stress compared to female floral counterparts, because ovule viability was affected by heat stress at p < 0.10 not at p < 0.05 like pollen (Jiang, et al., ).…”
Section: Discussionmentioning
confidence: 85%
“…However, our recent growth chamber studies showed that "CDC Sage" had more stable pollen surface and anther lipid composition compared to "CDC Golden," and "CDC Sage" had also a greater in vitro pollen germination percentage and pollen viability (Jiang et al, 2015;Jiang, et al, 2019).…”
Section: Plant Materialsmentioning
confidence: 95%
See 2 more Smart Citations
“…Understanding how heat stress influences reproductive organs is critical to improving grain legume yields in future climates. The study reported by Jiang et al () shows that heat stress exposure in pea leads to a greater inhibition of pollen development and viability than of ovules. A heat tolerant pea genotype was found to exhibit a more stable lipid composition in the stamens.…”
Section: Enhancing Stress Tolerancementioning
confidence: 95%